Building Entrepreneurial Capabilities in Scheduled Areas of Orissa - Singh, K. D.; Sinha, Bhaskar; Sutar, Pravat C. (Indian Forester, 2011)
People living in the forest fringe areas in Orissa mostly survive on subsistence agriculture and forest gathering with little of cash income from selling of non-timber forest produce through local traders (called middle men). The present study aimed to empower the local community to protect, manage and market the produce in a value added form. This report describes the study concerned with marketing of sal leaves. The aim was to find if local communities can run small scale enterprise for making of plates and cups from sal leaves and sell that in the open market with profit rather than dispose sal leaves in bundles to middle man at their doorsteps. The project supported buying of the equipment and limited training in plate and cup making and then let the community run the enterprise. The experience was positive showing that the products made by community were popular in the market and fetched good prices at the rates justifying the investments.